PARP4 deficiency enhances sensitivity to ATM inhibitor by impairing DNA damage repair in melanoma - Yuehua Li; Yu Liu; Jingjing Ma; Yuqi Yang; Qiao Yue; Guannan Zhu; Weinan Guo; Tianwen Gao; Qiong Shi; Chunying Li (Cell Death Discovery)
Abstract Besides the important pathogenic mechanisms of melanoma, including BRAF-driven and immunosuppressive microenvironment, genomic instability and abnormal DNA double-strand breaks (DSB) repair are significant driving forces for its occurrence and development. This suggests investigating novel therapeutic strategies from the synthetic lethality perspective. Poly (ADP-ribose) polymerase 4 (PARP4) is known to be a member of the PARP protein family. The low expression of PARP4 is significantly associated with defective DSB repair markers and poor prognosis in melanoma. Further research revealed that PARP4 plays a role in DSB repair by regulating the non-homologous end joining (NHEJ) pathway through its involvement in Ku80 mono-ADP-ribosylation. Moreover, from a synthetic lethality perspective, PARP4 expression is associated with ATM inhibitor sensitivity. Overall, our study provides new and valuable insights into the function of PARP4 and melanoma pathogenesis and suggests that ATM inhibitor may be a promising therapeutic approach for treating melanoma with low PARP4 expression.